Strategi Pengembangan Keagamaan Siswa SMP Plus - Anis Fauzi; Rosidah; Muhammad Akbar (JoIEM (Journal of Islamic Education Management), 2023)
This study aims to advise and foster SMP Plus Bina Insan Kamil students so that they can better understand how Islamic teachings should be used in their everyday lives both at school and outside of school. Duha prayer in congregation, reading Yaasin's letter after performing dhuha prayer, three language speech exercises (Indonesian, English, Arabic), Manaqiban activities, Tilawatil Al-Qur'an, activities Khataman Al-Qur'an, Mabit, and Islamic holiday activities are among the religious activities carried out by the Bina Insan Kamil Junior High School. This study employed a qualitative method with a descriptive approach. The study's data collection methods included observation, interviews, and documentation. While data reduction, data presentation, and drawing conclusions are all part of the analysis. According to the findings of this study, the growth of religious activities can generate motivation in terms of behaving or conducting activities in accordance with religious teachings. SMP Plus Bina Insan Kamil's method comprises habituation and demonstration by going through the steps of preparation, implementation, reflection, and evaluation. The existence of a plan for promoting religious activities is to create motivation in behaving according to religious teachings and Islamic religious law, as well as to motivate students to always read the Qur'an with Tajweed guidance in accordance with its norms. This can be demonstrated by observing changes in student attitudes during the learning process in the classroom. Collaboration among teachers, student interest, school norms, and adequate infrastructure are all supportive variables for this activity.